Prevalence of respiratory diseases and symptoms, in colonies hosting stone miners, in San Cristóbal de Las Casas, Chiapas, Mexico - Mazariegos García, Blanca Eneida; González Figueroa, Gerardo Alberto; Gutiérrez Villalpando, Verónica; Álvarez Gordillo, Guadalupe del Carmen; Salvatierra Izabá, Ernesto Benito (Población y Salud en Mesoamérica, 2022)
Introduction: The study estimated the prevalence rate of Acute Respiratory Diseases and Symptoms (ESRA) and its risk factors (RF), it was carried out in three host neighborhoods: Salsipuedes (200 households), San Miguel (35) and Ampliación San Miguel (9) from the southeast region of the city of San Cristóbal de Las Casas, Chiapas, Mexico, where the Salsipuedes stone mining company of sand and gravel for construction of roads and houses is located, for 35 years of extraction. Methodology: A cross-sectional epidemiological study was carried out, it began with a population census, where the survey was accepted in 156 (63.9 % of the total) and a structured questionnaire with closed and open questions was applied to an adult of each family. The questions were oriented to identify the signs and symptoms of incident and prevalent diseases (closed questions), on the other hand, six open qualitative questions related to how do you consider the activity of the sandbank that exists in your neighborhood?, to identify the perceptions of the risk for social, environmental and health damages, and whether or not they associated them with living in those neighboring host neighborhoods of the mining company. Results: The prevalence rate of ESRA in Salsipuedes was 5.6%, San Miguel 12.0% and Ampliación San Miguel 21.9% (total TP=7.6%) (p ≤ 0.05); Nine socioeconomic variables were explored, of which five (wooden wall of the house, proximity to the neighborhood, proximity to the international highway, home ownership and health perception) were statistically associated with stone mining activity with a significance value statistic of (p ≤ 0.05). Conclusions: Mining activities had an impact on ESRA associated with the proximity and conditions of housing and also influenced negative perceptions of health and the environment.